Development of a Drosophila Cell-Based Error Correction Assay - Salemi, Jeffrey D.; McGilvray, Philip T.; Maresca, Thomas J. (Frontiers in Oncology, 2013)
Accurate transmission of the genome through cell division requires microtubules from opposing spindle poles to interact with protein super-structures called kinetochores that assemble on each sister chromatid. Most kinetochores establish erroneous attachments that are destabilized through a process called error correction. Failure to correct improper kinetochore-microtubule (kt-MT) interactions before anaphase onset results in chromosomal instability (CIN), which has been implicated in tumorigenesis and tumor adaptation. Thus, it is important to characterize the molecular basis of error correction to better comprehend how CIN occurs and how it can be modulated. An error correction assay has been previously developed in cultured mammalian cells in which incorrect kt-MT attachments are created through the induction of monopolar spindle assembly via chemical inhibition of kinesin-5. Error correction is then monitored following inhibitor wash out. Implementing the error correction assay in Drosophila melanogaster S2 cells would be valuable because kt-MT attachments are easily visualized and the cells are highly amenable to RNAi and high-throughput screening. However, Drosophila kinesin-5 (Klp61F) is unaffected by available small molecule inhibitors. To overcome this limitation, we have rendered S2 cells susceptible to kinesin-5 inhibitors by functionally replacing Klp61F with human kinesin-5 (Eg5). Eg5 expression rescued the assembly of monopolar spindles typically caused by Klp61F depletion. Eg5-mediated bipoles collapsed into monopoles due to the activity of kinesin-14 (Ncd) when treated with the kinesin-5 inhibitor S-trityl-L-cysteine (STLC). Furthermore, bipolar spindles reassembled and error correction was observed after STLC wash out. Importantly, error correction in Eg5-expressing S2 cells was dependent on the well-established error correction kinase Aurora B. This system provides a powerful new cell-based platform for studying error correction and CIN.